APPLICATION MULTIPLEX PCR FOR EARLY DETECTION ESCHERICHIA COLI CONTAMINATION IN SOME DRINKING WATER RESOURCES IN ABEPURA, PAPUA INDONESIA - Mawardi, Arsyam; Budi, I Made; Lantang, Daniel (Jurnal Pendidikan Matematika dan IPA, 2023)
Abstract Microbial detection takes a long time to produce positive results, so a quicker detection method was chosen. Multiplex polymerase chain reaction (m-PCR) identified bacterial strains in less than 24 hours, detects E.coli specifically, and is faster than traditional methods. The goal of this study was to use m-PCR to detect early pathogenic E.coli bacteria in several drinking water sources in the Abepura district of Papua Indonesia as a parameter of pollution and water quality. The Chelex100 and microwave combination method was used to extract DNA. The first round of testing was done at four different concentrations: 0.125, 0.250, 0.375, and 0.500 M. The purity of the extracted DNA was good, ranging from 1.80 to 1.94. The optimum primer concentration for multiplexing applications is 0.25 uM for lt primer; 0.125 uM for stx2 and eae primer, with an annealing temperature of 55oC. m-PCR has been shown to quickly detect pathogenic E. coli in water samples. In the PCR process, E.coli DNA template was obtained with high purity (1.80-1.94) and concentration (576.9-4301.6 ng/uL) .   Each multiplex set included three primer pairs for the target gene lt-eae-stx2 on ETEC-EPEC and EHEC respectively. The m-PCR process showed excellent results, and this findings can be considered as a reference for water analysis in several drinking sources in Papua Province.